Moving beyond adjunctification in Portugal’s universities: Research and Development Unit Directors’ perspectives - Cairns, D. (Higher Education Policy)
This article addresses an important development relating to Research and Development (R&D) units in Portugal’s universities. In recent years, higher education policy in this country has been gradually moving away from supporting what has been conceptualised by certain stakeholders as a ‘soft institution’ model, reliant on the contributions of teaching staff and fixed-term contract workers, towards recognising a need for the tenured employment of dedicated researchers. At a theoretical level, this situation is interpreted as movement away from the adjunctification of researchers and R&D units in universities due to the strong associations with precarity that the research profession has acquired, a proposition explored through discussing evidence from a study conducted in 2023 that included interviews with the directors of 28 R&D units. These interviewees explain how their own careers developed and why the ‘soft institution’ model emerged in this national context, illustrating the attractions and limitations of the approach. More specifically, findings bring to light concerns regarding the ability of some units to remain competitive, and recruit and retain sufficient numbers of researchers with a strong fundraising capacity.